Principles of Diagnosis and Therapy of Bronchial Asthma in Children at the Present Stage: GINA 2014-2015 Review Updates - L. R. Selimzyanova; E. A. Vishneva; E. A. Promyslova (Union of pediatricians of Russia, 2015)
Bronchial asthma is one of the most prevalent breathing illnesses. Today there is a sufficiently wide spectre of effective medicines with a good safety profile and an acceptable price. Despite this, a large number of patients receive inadequate treatment, which leads to a decrease in life quality, permanent bronchial obstruction and even death. In 2014 the Global Initiative for Asthma (GINA) significantly renewed its regularly issued Global Strategy for Asthma Management and Prevention. It includes relevant asthma information together with practical clinical recommendations. This article highlights the renovations published in the document in 2014 and 2015. The authors present modern approaches to child bronchial asthma diagnosis, including differential, together with the actualized treatment goals and principles. The criteria for evaluating the disease control and child asthma severity are also covered. The possible problems of achieving adequate control of the disease are also analyzed.